2017
DOI: 10.2334/josnusd.16-0666
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength of universal adhesives to air-abraded zirconia ceramics

Abstract: The bond strength of universal adhesives to air-abraded zirconia ceramic was evaluated. Overall, 40 zirconia ceramic blocks with dimensions of 6 × 6 × 4 mm were cut from pre-sintered blanks. The sintered blocks were embedded in self-cured acrylic resin. The zirconia blocks were then randomly allocated to four groups (n = 10) in which different universal adhesives were used, except for the control group in which no universal adhesive was used. A silicon mold was used to build the resin cement. All specimens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…The results of the current study is in accordance with Wolfart et al (8) , Nothdurft et al (48) , Taniş et al (21) , Visuttiwattanakorn et al (14) , Al Jeaidi et al (49) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the current study is in accordance with Wolfart et al (8) , Nothdurft et al (48) , Taniş et al (21) , Visuttiwattanakorn et al (14) , Al Jeaidi et al (49) .…”
Section: Discussionsupporting
confidence: 92%
“…The reason for that might be due to the higher viscosity of Panavia F2.0 cement than Single bond universal adhesive and this proved with SEM. The adhesive used with RelyX Ultimate penetrate more into irregularities created by air abrasion and could promote better surface wettability (46,49) . This was in agreement with Rohr N. (47) as he reported in a study, that MDP in primer showed significant difference than that of cement in improving bond strength of zirconia by increased wettability.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical bonding promoted by 10‐MDP is more effective and stable in water than that provided by other functional monomers . Additionally, 10‐MDP has been shown to chemically bond with the oxides in zirconia while copolymerizing with resin monomers of the luting cement . Glycero‐phosphate dimethacrylate (GPDM) is another functional monomer that forms a calcium salt with hydroxyapatite though the bond is not stable .…”
Section: Resultsmentioning
confidence: 99%
“…Many MDP‐based UAs have also been recommended for effectively bonding zirconia . Adequate bonding with UAs still requires prior abrasive surface treatment and although acceptable bond strengths were achieved in the short‐term, their durability after artificial‐aging was found to be questionable . One study suggested silica coating followed by heat treated ceramic primer or a MDP‐based UA to improve the bond durability .…”
Section: Resultsmentioning
confidence: 99%
“…Resultados semelhantes foram encontrados por Arpa et al, quando utilizaram o SBU para reparar resina composta para CAD-CAM, sem o emprego de nenhum tratamento mecânico da superfície 13. O SBU possui uma molécula de MDP, um monômero funcional capaz de se ligar diretamente aos óxidos de zircônia através de um grupo éster fosfato,80,108 ao mesmo tempo que se liga a matriz da resina através de um grupo metacrilato 81,82. De acordo com o fabricante, a resina composta Filtek One Bulk Fill possui partículas de zircônia em sua composição, além das partículas de sílica convencionais.…”
unclassified